A variance components approach to food grain market integration in Northern Nigeria - Delgado, Christopher L. (Wiley, 1986)
A variance components methodology is developed for joint tests on a sample of time series of prices for seasonal differences in the price integration of markets. The approach requires a statistically adequate number of observations for each market within seasons characterized by constancy of transactions costs among markets. The model is applied to eighteen months of weekly grain prices for twenty‐two villages in northern Nigeria. Results suggest that markets are not well integrated in the six months covering the harvest period. Implications are drawn for research on market performance in the region.